“Setan Makan Babi”: Narasi Woodard dan Masyarakat Muslim di Pesisir Teluk Palu dan Jaringannya Akhir Abad XVIII - Mohammad Nur Ahsan (Department of History, Faculty of Humanities, Diponegoro University, 2022)
This article discusses Muslim communities in the coastal area of Palu Bay in the late eighteenth century. Historiographical sources from scholars and historians regarding Islam in this region generally state that the teachings of this religion were first disseminated in the early seventeenth century thanks to the role of the Minangkabau cleric, Abdullah Raqie, or known as Datokarama. However, from the Datokarama period to the nineteenth century, Islamic historiography appears to be inadequate due to limited access to primary sources dating from the same period as the events studied and the tendency to oral traditions that require critical formulation. This article uses historical methods to reconstruct the Muslim community in the coastal area of Palu Bay based on records from European sailors who had lived in Sulawesi and made voyages through maritime routes connecting the islands in northern Kalimantan to Papua. Apart from showing characteristics of the local Muslim community during this period, the article shows that the role of Ismail Tuan Haji as the highest imam for the community and the king's authority in Donggala is an indication of the network of spreading Islam in this region connected to the Sultanate of Sulu and Mindanao. Simultaneously, the network confirmed the route navigation map to the East from the Ming Dynasty, dating back to the early fifteenth century.